2011
DOI: 10.1037/a0021479
|View full text |Cite
|
Sign up to set email alerts
|

The sense of entitlement in romantic relationships—Scale construction, factor structure, construct validity, and its associations with attachment orientations.

Abstract: Based on clinical evidence and theoretical writings that pointed to the importance and uniqueness of the sense of entitlement in couple relationships, two studies were designed to develop and validate the Sense of Relational Entitlement (SRE) scale. A factor analysis performed on the scale's items yielded five factors that identified three basic entitlement-related attitudes toward a romantic partner. Findings indicated that both exaggerated and restricted forms of relational entitlement seem to be maladaptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
145
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(160 citation statements)
references
References 53 publications
13
145
2
Order By: Relevance
“…Entitlement Attitude Scale; Nadkarni, 1994), mostly in clinical contexts or within narrowly specified fields (e.g. Sense of Relational Entitlement Scale; Tolmacz & Mikulincer, 2011; Exploitive and Non-Exploitive Entitlement Scale; Lessard et al, 2011). To the best of our knowledge, there are no existing methods of examining entitlement from a social and adaptive personality psychology perspective that have been validated internationally.…”
Section: Measurement Of Entitlementmentioning
confidence: 99%
“…Entitlement Attitude Scale; Nadkarni, 1994), mostly in clinical contexts or within narrowly specified fields (e.g. Sense of Relational Entitlement Scale; Tolmacz & Mikulincer, 2011; Exploitive and Non-Exploitive Entitlement Scale; Lessard et al, 2011). To the best of our knowledge, there are no existing methods of examining entitlement from a social and adaptive personality psychology perspective that have been validated internationally.…”
Section: Measurement Of Entitlementmentioning
confidence: 99%
“…Tolmacz and Mikulincer (2011) have stressed that entitlement plays an especially important role in a couple's relationship. From the perspective of personality psychology and according to Bowlby's attachment theory (Bowlby, 1979), perceptions and memories of the type or quality of care that individuals received from early attachment figures shape the way they respond to tiieir attachment figures in adulthood.…”
Section: Sense Of Relational Entitlementmentioning
confidence: 99%
“…Rather, one's sense of relational entitlement may be comprised of botii assertive and conflicted aspects concurrently. Tolmacz and Mikulincer (2011) claimed that relational entitlement is a personality construct deriving from early relationships with primal attachment figures. Indeed, the authors reported on significant associations among attachment avoidance and anxiety orientations on the one hand and items representing excessive and restricted entitlement (that we later labeled "conflicted entitlement") on the other hand.…”
Section: Sre-scale Validationmentioning
confidence: 99%
See 2 more Smart Citations